TÜRKİYE'DE DOĞADA VARLIĞI KANITLANAN HISTOPLASMA CAPSULATUM: ÖNEMİ - YÜCEL, Ayhan; KANTARCIOĞLU, A. Serda (Cerrahpaşa Medical Journal, 2014)
Background.. Histoplasma capsulatum has become an increasingly frequent opportunistic infection among patients whose immune system is impaired either by infection with human immunodeficiency virus (HIV) or by other factors. Because of the existence of this primary pathogen fungus in nature in Turkey has been shown, the possibility of recovering the cases of histoplasmosis and some important notes concerning on its diagnosis have been discussed in the paper.